Overview of Public Knowledge Towards the Prevention of COVID-19 Transmission at Environment IV of Sidikalang Village 2022 - Rusmauli Lumban Gaol; Cindy Rutfani Hutauruk (Jurnal EduHealth, 2022)
Coronavirus is part of a large family of viruses that cause diseases that occur in animals or humans. Humans who contract the virus will show signs of respiratory infections ranging from the flu to more serious ones. Prevention of covid-19 transmission can be done starting from washing hands, using masks, social distancing, physical distancing, applying coughing and sneezing etiquette, implementing a clean and healthy lifestyle, changing clothes, managing comorbidities, managing mental health &psychosocial health and implementing adaptation to new habits of carrying out health protocols. The purpose of the study is to find out a picture of public knowledge about preventing the transmission of COVID-19 at Environment IV of Sidikalang Village. This study uses a descriptive design with sampling techniques using purposive sampling of 65 respondents. The results show that the picture of public knowledge about the prevention of COVID-19 transmission at Environment IV of Sidikalang Village was obtained "good" 24 people (36.9%), "enough" 39 people (60.0%) and "less" 2 people (3.1%). It is hoped that the public can further increase awareness in implementing the prevention of COVID-19 transmission recommended by the government in daily life.